Efficacy of SEBCLAIRA® Cream for Moderate Seborrhoeic Dermatitis on The Face as An Adjuvant Therapy (Randomised Clinical Trial, Double Blind) - Inda Astri Aryani; Yulia Farida Yahya; Nina Roiana; Radema A Pranata (HM Publisher, 2018)
Background: Seborrhoeic dermatitis (SD) is a chronic papulosquamous inflammatory disease which resistant to medical treatment. Various treatment such as topical corticosteroid, antifungal and calcineurin inhibitor has been widely practiced and gives varying results Objective: Our objective was to compare the efficacy of Sebclaira® and topical hydrocortisone 2,5% for management of moderate SD on the face Methods: A randomised clinical trial, controlled, double blind study was performed for four weeks. We assessed the efficacy and side effects of these topical treatment. The severity of SD was evaluated using Seborrhea Area Severity Index-Facial (SASI-F) score. The severity of pruritus was evaluated using Visual Analogue Scale. Demographic characteristics, baseline SASI-F and VAS were recorded in the medical record. Results: A 34 patients (14 males, 20 females) with moderate SD on the face completed the four weeks study. The mean of SASI T2 and VAS score of the Sebclaira® group was significantly lower than Hydrocortisone 2.5% group with p = 0.000 and p = 0.000 respectively. Tolerance between Sebclaira® and Hydrocortisone 2.5% showed insignificant results (p = 1.000) Conclusions: The longer application of Sebclaira® was significantly more effective to improve moderate SD